MON-022 Dissecting the Interplay Between Diet and PCOS Pathology on Gut Microbiota in a PCOS Mouse Model - Paris, Valentina Rodriguez (J Endocr Soc, 2020)
The gut microbiome has been implicated in the development of metabolic disorders such as obesity and type-2 diabetes, and more recently polycystic ovary syndrome (PCOS). PCOS is a heterogeneous disorder with reproductive, endocrine and metabolic irregularities, and clinical and animal studies have reported that PCOS causes a decrease in microbial diversity and composition. Diet is an important regulator of the gut microbiome, and a recent study identified that alterations in macronutrient balance impact gut microbial communities which correlate with different metabolic health outcomes (1). We have identified that macronutrient balance impacts the development of PCOS traits. Therefore, to investigate the interplay between macronutrient balance and a PCOS environment on the gut microbiome, we analyzed the intestinal microbiome from fecal pellets of control and DHT-induced PCOS mice exposed to 10 different diets that varied systematically in protein (P), carbohydrate (C) and fat (F) content. The amount of dietary P, C and F consumed significantly altered alpha and beta diversity of the gut microbiota of pooled control and PCOS mice (P<0.0001). Alpha diversity between control and PCOS mice on the same diet did not differ significantly, and hence was only affected by diet composition. However, beta diversity was significantly altered between control and PCOS mice (P<0.05). We performed DESeq2 analysis and identified an operational taxonomic unit (OTU) within Bacteroides (OTU3) to be the most differentially abundant OTU between control and PCOS mice, with a significant decrease in PCOS mice compared to controls (control: 7.88 and PCOS: 5.38; fold change = 1.464; P<0.0001). The consensus sequence of Bacteroides OTU3 was found to share 99.2% similarity to Bacteroides acidifaciens. B. acidifaciens is associated with obesity with elevated levels reported to prevent the onset of obesity (2). Thus, we then investigated the influence of P, C and F on the relative abundance of Bacteroides OTU3 and revealed an association with C consumption, with increasing levels of C leading to increased levels of Bacteroides OTU3 (Carb: r= 0.22, p=0.0028, q=0.015). These findings demonstrate that diet exerts a stronger influence over the gut microbiome than PCOS pathology. However, the hyperandrogenic PCOS environment does lead to changes in gut microbiota beta diversity, with a specific decrease in an obesity-associated (2) Bacteroides species in PCOS mice that is also responsive to levels of C consumption. Reference: (1) Holmes et al., Cell Metabolism. 2017; 25(1): 140-151. (2) Yang et al., Mucosal Immunology. 2017, 10 (1), 104-116.